Linear endosonography in lung cancer - Bugalho, Antonio (2022)
The role of endobronchial ultrasound (EBUS) and trans-esophageal endobronchial ultrasound (EUS-B) in lung cancer is well established and scientifically validated. There is increasing data that endosonography is a crucial tool for the diagnosis of central lung lesions, and mediastinal staging and restaging of non-small cell lung cancer patients. The present article reviews the technical aspects of EBUS and EUS-B and focus on the last published research regarding its value in lung cancer.